FORMING THE CHARACTER OF TOLERANCE AND SOCIAL CARE IN CLASS III STUDENTS AT SDN GAYUNGAN 2 SURABAYA - Maria Herawati Suni; Apri Irianto (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The researcher's aim is to describe how to form and what are the obstacles in the character of tolerance and social care in class III at SDN Gayungan II Surabaya. This research uses a qualitative approach. The research aims to understand the phenomena experienced by research subjects, for example behavior, perception, motivation, and by means of descriptions in the form of words and language, in a special natural context and by utilizing various scientific methods. There are many observation results. There is a program that is run at SDN Gayungan 2 Surabaya, such as getting used to saying hello in the morning in front of the school gate, on Monday there is a flag ceremony, on Tuesday there is a remo dance, on Wednesday there is an I can activity, on Thursday there is reading Asmaul Husna, on Friday there is jumberling (clean Friday around. Based on the results of the research and discussion, it can be concluded as follows: 1. Forming the character of class 3 is not as easy as expected because at the age of class 3 students are still in the low class, in forming the character of students, cooperation also needs to be increased good relationship and establishing a good relationship with parents or guardians of students to be able to entrust the school and homeroom teacher in forming the character of students in class.